Autowave process of the localized plastic deformation of high-chromium steel saturated with hydrogen; Journal of Physics: Conference Series; Vol. 722 : Nonlinear Waves: Theory and New Applications (Wave16) - Bochkareva A. V. Anna Valentinovna; Barannikova S. A. Svetlana; Li Yu. V. Yuliya Vladimirovna; Lunev A. G. Alexey Gennadievich; Zuev L. B. Lev Borisovich (2016, 2016)
Title screen